STRATEGI KONSEPTUAL DAN SIMULASI VISUAL AUGMENTED REALITY SEBAGAI MEDIA WAYFINDING DAN EDUKASI BUDAYA DI KAMPUNG NAGA - Sayogo, Dwisanto; Sunarmi; Santosa (AKSA: Jurnal Desain Komunikasi Visual, 2025)
This study aims to design a conceptual strategy and visual simulation for the use of Augmented Reality (AR) as a medium for wayfinding and cultural education in Kampung Naga, a traditional village in West Java that strictly preserves its cultural heritage. The lack of spatial and cultural information available to visitors, due to local restrictions on digital infrastructure, highlights the need for an innovative approach that respects local customs. Employing a qualitative-critical method through observation and literature review, this research proposes a simulated AR interface design featuring interactive navigation, culturally integrated non-invasive markers, and educational overlays about local architecture and performing arts such as Terbang Gembrung. The results suggest that a context-aware, adaptive, and non-intrusive AR design can enhance the visitor experience while preserving the authenticity of traditional spaces. This study recommends AR integration as an educational and navigational solution for sustainable and culturally respectful heritage tourism development.